Study of the price variation analysis of proton pump inhibitors available in Indian pharmaceutical market - Bhushan, Rabi; Kishore, Anupam; Chandra, Akash; Kumar, Ajay; Singh, Haribansh kumar (International Journal of Research in Medical Sciences, 2020)
Background: In now day’s proton pump inhibitors are prescribing more and more by Indian physicians not only in peptic ulcer, gastroesophageal reflux disease, gastritis but also along with non-steroidal anti-inflammatory drugs to overcome the side effects as gastric irritation and discomfort by non-steroidal anti-inflammatory drugs. There are many brands of PPI drugs available in Indian market. Costly drugs can lead to economic burden which results in decreased compliance or even non-compliance. Non–compliance leads to incomplete treatment which tends to increase morbidity. Increase in the patient medication cost was found to associated with decreased adherence to prescription medication. Hence this study was done to assess the cost variation of proton pump inhibitors (PPI) drugs. Methods: The maximum and minimum price of each brand of the drug in INR was noted by using Drug Today January to April 2020 edition, Vol-1. The cost ratio and the percentage cost variation for individual drug brands was calculated. The cost of 10 tablets/capsules was calculated in case of oral drug. At last the cost ratio and percentage cost variation of various brands was compared. Results: Percentage variation in cost for proton pump inhibitors marketed in india was found to be tablet/capsule Esomeprazole [20mg]: 297.65, tablet/capsule Esomeprazole [40mg]: 344.41, capsule/tablet Omeprazole [10mg]: 74.51, capsule/tablet Omeprazole [20mg]: 542, Tablet/capsule Pantoprazole [40mg]: 3297.33, tablet/capsule Rabeprazole [10mg]: 1160, tablet/capsule Rabeprazole [20mg]: 1101.05, capsule/tablet Lansoprazole [15mg]: 306.69, capsule/tablet Lansoprazole [30mg]: 336.33, capsule/tablet Dexlansoprazole [60mg]: 7.69. Conclusions: Capsule Pantoprazole [40mg] shows highest cost ratio and percentage cost variation as 33.97 and 3297.33. While capsule Dexlansoprazole [60mg] shows lowest cost ratio and percentage cost variation as 1.07 and 7.69.